Meanings & Co. The Interdisciplinarity of Communication, Semiotics and Multimodality - Olteanu, Alin; Stables, Andrew; Borţun, Dumitru (Numanities - Arts and Humanities in Progress, 2019)
This book explores the interdisciplinarity of semiotics and communication studies, comprising both theoretical explorations and semiotic applications to communication with theoretical bearings. These disciplines have generally been understood as mutually implicit, but there still are many unexplored research avenues in this area, particularly on a conceptual level. The book offers broad insights into the epistemological relations between semiotics and other approaches to communication from perspectives such as sociology, philosophy of language and communication theory. As such, it sheds light on the communication of knowledge. Semiotics is currently enjoying increasing popularity within the humanities and social sciences. Understood as relational logic (Charles Peirce) or hermeneutics (structuralism and poststructuralism), semiotics fundamentally implies certain positions with regard to communication. Because of the generality and conceptual vagueness of semiosis and communication, how one elucidates the other is still an underexplored theme. With some pioneering studies of this relation, the books examines various fields, such as language, code, learning, embodiment, political communication, media, cinema, cuisine, multimodality and intertextuality.